Comparison of Islamic Family Law in Malaysia and Indonesia - Ade Khoirunnisa; Retno Arimbi Dewi; Fatya Zahra Siahaan; Siti Samra; Aulil Amri (An-Nisa: Journal of Islamic Family Law, 2025)
Islamic family law in Malaysia and Indonesia has the same sharia basis but differs in its application due to the influence of the legal system, culture, and state policies. This comparison is important to understand the variation of regulations and their implications for Muslim communities in both countries. This study aims to analyze the similarities and differences of Islamic family law in Malaysia and Indonesia, especially in the aspects of marriage, polygamy, and inheritance, and to examine the effectiveness of its implementation. This study uses a normative juridical method with a comparative approach. Primary data sources include the Enakmen of the Melaka State Law Number 12 of 2002, the Selangor State Law Draft, the Islamic Family Law Enakmen Number 17 of 2003 (Malaysia), and Law Number 1 of 1974, Law Number 16 of 2019, and the Compilation of Islamic Law (Indonesia). Data collection techniques were carried out through library research, with data analysis using descriptive analysis and content analysis of applicable legal provisions. Research shows that although Malaysia and Indonesia are both based on sharia, Malaysia tends to be more structured in regulating polygamy and inheritance, while Indonesia is more flexible by considering customary law. Differences are also seen in the authority of the judicial institution, where Malaysia has autonomous Sharia Courts per state, while Indonesia implements a centralized system through the Religious Courts.